2016
DOI: 10.7454/jpdi.v3i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Prediktor Mortalitas Pasien HIV/AIDS Rawat Inap

Abstract: Pendahuluan. Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) adalah masalah besar yang mengancam Indonesia dan banyak negara di seluruh dunia. Pengetahuan tentang karakteristik dan prediktor mortalitas dapat membantu dalam penatalaksanaan pasien. Penelitian ini bertujuan untuk mengetahui faktor-faktor prediktor mortalitas pasien HIV/AIDS dewasa yang dirawat di RSUPN Dr. Cipto Mangunkusumo (RSCM).Metode. Penelitian ini merupakan studi kohort retrospektif pada pasien rawat inap dewasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
1
5
1
6
Order By: Relevance
“…Multivariate analysis done in this study showed that impaired renal function had a significant correlation to HIV/AIDS patients' mortality with an OR 2.646 (95% CI 1.314-5.328). This study supported the research conducted in Jakarta [6] as well as the research conducted by Wyatt et al However, there was a slight difference between the result of this study and a study conducted by Wyatt et al Categorized into acute renal failure and chronic kidney disease, Wyatt et al study stated that acute renal failure ( OR=5.84; 95% CI 5.11-6.65) possessed higher mortality risk compared to chronic kidney disease (OR=1.97%; 95% CI 1.59-2.45) [28].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Multivariate analysis done in this study showed that impaired renal function had a significant correlation to HIV/AIDS patients' mortality with an OR 2.646 (95% CI 1.314-5.328). This study supported the research conducted in Jakarta [6] as well as the research conducted by Wyatt et al However, there was a slight difference between the result of this study and a study conducted by Wyatt et al Categorized into acute renal failure and chronic kidney disease, Wyatt et al study stated that acute renal failure ( OR=5.84; 95% CI 5.11-6.65) possessed higher mortality risk compared to chronic kidney disease (OR=1.97%; 95% CI 1.59-2.45) [28].…”
Section: Discussionsupporting
confidence: 86%
“…This condition can increase the cardiovascular risk which leads to morbidity and mortality [30]. Disorders of electrolytes or acid base and fluid retention in impaired kidney function can also increase the mortality risk [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data Global tuberculosis report 2019 menyebutkan dari 1,2 juta orang yang baru mendaftar perawatan HIV pada 2018, 8% diantaranya didiagnosis TB ditahun yang sama dan secara global tercatat ada 477,461 penderita HIV yang mengalami TB (World Health Organization, 2019). Dalam penelitian yang dilakukan Puspitasari et al, (2016) pada 606 pasien HIV/AIDS di Rumah Sakit dr. Cipto Mangunkusumo (RSCM) Jakarta dengan HIV/AIDS selama tahun 2011-2013 ditemukan ada 131 kematian akibat AIDS dengan 23,9% diantaranya disebabkan TB paru.…”
Section: Pendahuluanunclassified
“…The causing factors of HIV transmission are multiple sexual partners, injecting drug users, transmission of homosexual partners, and blood transfusions. As the disease progresses, the immune system decreases so people with HIV / AIDS are susceptible to various opportunistic infections (Puspitasari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%